2017
DOI: 10.4238/gmr16029541
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL1 transcript types showed distinct laboratory characteristics in patients with chronic myeloid leukemia

Abstract: ABSTRACT. In chronic myeloid leukemia (CML) two main types of messenger RNA (e14a2 and e13a2) can be produced by BCR-ABL1 gene rearrangement. Due to conflicting results, the clinical value of these transcripts remains controversial. The aim of this study was to identify associations of e14a2 and e13a2 transcripts with laboratory variables and also the response to treatment. This study included 203 adult patients with CML treated with Imatinib as first-line drug in a reference hematology center in Northeast Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
4
9
1
Order By: Relevance
“…21 In nearly all the studies, sex did not appear to have an impact on the transcript types, including the European LeukemiaNet (ELN) cohort, which to our knowledge has the largest sample size. 2,[22][23][24][25][26][27][43][44][45][46][47][48] However, a small study consisting of 43 patients from Sudan with CML demonstrated a possible relationship between the e13a2 transcript and male sex, 20 which then was confirmed by other 2 large-scale studies from Italy (559 patients) 28 and India (200 patients) 29 (P 5.03 and P 5.05, respectively). In addition, Lin et al 30 demonstrated that female sex was more frequent among patients coexpressing both the e13a2 and e14a2 transcripts (P<.05), although no significant difference with regard to sex was shown in the e13a2 or e14a2 transcript groups.…”
Section: Relationship Between Transcript Types and Patient Characterimentioning
confidence: 92%
See 4 more Smart Citations
“…21 In nearly all the studies, sex did not appear to have an impact on the transcript types, including the European LeukemiaNet (ELN) cohort, which to our knowledge has the largest sample size. 2,[22][23][24][25][26][27][43][44][45][46][47][48] However, a small study consisting of 43 patients from Sudan with CML demonstrated a possible relationship between the e13a2 transcript and male sex, 20 which then was confirmed by other 2 large-scale studies from Italy (559 patients) 28 and India (200 patients) 29 (P 5.03 and P 5.05, respectively). In addition, Lin et al 30 demonstrated that female sex was more frequent among patients coexpressing both the e13a2 and e14a2 transcripts (P<.05), although no significant difference with regard to sex was shown in the e13a2 or e14a2 transcript groups.…”
Section: Relationship Between Transcript Types and Patient Characterimentioning
confidence: 92%
“…However, in their study, the German investigators demonstrated that patients with the e13a2 transcript had significantly higher baseline median leukocyte counts compared with patients with the e14a2 transcript (88 × 10 9 /L vs 65 × 10 9 /L; P <.001), but no such relationship was shown for hemoglobin levels . A recently published study from Brazil also reported similar findings and patients with the e13a2 transcript had a significantly higher median leukocyte count at the time of diagnosis compared with patients with the e14a2 transcript (147 × 10 9 /L vs 129 × 10 9 /L; P = .049) (Table ) …”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations